A NEW PRINCIPLE FOR CREATING A BIOLOGICALLY ACTIVE ADDITIVE TO FOOD USED IN THE TREATMENT AND PREVENTION OF VIRAL DISEASES (Scientific journal of the Fergana State University, 2025)
Using HPLC and instrumental neutron activation analysis, the above-ground parts of Matricaria recutita L. (1), Taraxacum officinale Wigg. s. L. (2), Cichonum intubus L. (3), Herba Origani vulgaris (4), Tribulus terrestris L. (5), Leonurus cardiaca L. (6) and Melissa officinalis L. (7) grown in the Fergana Valley were studied to contain chemical components such as amino acids (cysteine, histidine), vitamins (ascorbic acid, P), flavonoids (quercetin, rutin) and bioelements (zinc, iron, selenium, magnesium). A high content of antiviral components was found in all the plants studied, which made it possible to create a biologically active food supplement (BAA) based on the seven plants, which has antiviral, antimicrobial and immunomodulatory effects.